The Effect of Civil Servants’ Service Quality on Public Satisfaction at the Regional Agency for National Unity and Politics of Tabalong Regency - Fatmawati; Misransyah Akos; Anhar Yani; Muhammad Jayadi; Septeria Noor Yuliannisa (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
This study examines the effect of apparatus service quality on community satisfaction at the National Unity and Politics Agency (Bakesbangpol) of Tabalong Regency, specifically in the context of the Registered Certificate (Surat Keterangan Terdaftar/SKT) service. Service quality was measured using the SERVQUAL model encompassing five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. A quantitative approach with multiple linear regression analysis was employed. The research involved 59 respondents selected from the community who had received SKT services. Data were collected through structured questionnaires and analyzed using SPSS version 26. The results reveal that: (1) partially, tangibles (t=2.491, sig.=0.016), responsiveness (t=2.585, sig.=0.013), and assurance (t=3.275, sig.=0.002) have a positive and significant effect on community satisfaction, while reliability (t=-1.308, sig.=0.197) and empathy (t=-0.440, sig.=0.661) do not have a significant effect; (2) simultaneously, all five dimensions significantly influence community satisfaction (F=12.931, sig.=0.000); and (3) assurance is the dominant variable influencing community satisfaction with a standardized coefficient of 0.681. These findings emphasize the importance of enhancing staff competence, trustworthiness, and service assurance to improve public satisfaction in government administrative services.